Nepal Engaging the Private Sector in Education : SABER Country Report 2016 - World Bank Group (World Bank, Washington, DC, 2017)
This report presents an analysis of how effectively the current policies in Bangladesh engage the private sector in basic (primary and secondary) education. The analysis draws on the Engaging the Private Sector (EPS) framework, a product of the World Bank’s Systems Approach for Better Education Results (SABER). SABER collects and analyzes policy data on education systems around the world, using evidence-based frameworks to highlight the policies and institutions that matter most for promoting learning for all children and youth. The rest of the report provides an overview of SABEREPS, followed by a description of the basic education system in Nepal, with a focus on the private sector and government policies related to the private provision of education. The report then benchmarks Nepal’s policy environment utilizing the SABER-EPS Framework, and offers policy options to enhance access and learning for all children in primary and secondary school.